2011
DOI: 10.1088/1748-6041/6/3/031001
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of growth and differentiation of C2C12 skeletal muscle cells on PSS–PAH-based polyelectrolyte layer-by-layer nanofilms

Abstract: Polyelectrolyte layer-by-layer (LbL) nanofilms are interesting polymeric structures, built by alternating adsorption of positively and negatively charged polyelectrolytes. They consist of multilayer sheets with nanometric overall thickness, and they can be used as supports and surface coatings for in vitro and in vivo cell and tissue growth and regeneration. The present study focuses on nanofilms based on alternated layers of poly(sodium-4-sulfonate) (PSS) and poly(allylamine hydrochloride) (PAH) fabricated us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 29 publications
1
31
0
Order By: Relevance
“…This was quantified by determination of fusion index and total myotube area (Fig. 4C,D) using established approaches (Ricotti et al, 2011). To examine possible effects of miR-1/miR-206 inhibition after the onset of differentiation, we modified miRNA levels, by antimiR-206 transfection at day 3 (in DM).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was quantified by determination of fusion index and total myotube area (Fig. 4C,D) using established approaches (Ricotti et al, 2011). To examine possible effects of miR-1/miR-206 inhibition after the onset of differentiation, we modified miRNA levels, by antimiR-206 transfection at day 3 (in DM).…”
Section: Discussionmentioning
confidence: 99%
“…For adipogenic differentiation, C2C12 cells were grown to confluency in GM and switched to an adipogenic medium as described (Akimoto et al, 2005). Apoptosis was induced by 2 mM H 2 O 2 for 6 hours as described (Salucci et al, 2010).…”
Section: Dna Constructs and Luciferase Assaymentioning
confidence: 99%
“…However, up to date, few studies have combined this effect with the skeletal muscle behavior. In particular, different surface charges of a layer-by-layer polyelectrolyte on C2C12 skeletal muscle cells for skeletal 55 muscle regeneration capabilities was studied and it has been shown that negatively charged surfaces supported higher cell attachment than positively charged ones 49 .…”
mentioning
confidence: 99%
“…Confluent cultured of C2C12cells washed with PBS, detached from petri dish by trypsinizing (.25% trypsin, Sigma Co., St. Louis, MO). Trypsinated cell-medium solution was centrifuged to get cell pallet to seed cell on the PV devices @ 12,000/cm 2 [17]. The cell cultures were maintained in DMEM growth medium and incubated maintaining 5% CO 2 atmosphere at 37°C, and 100% humidity.…”
Section: Methodsmentioning
confidence: 99%